The Effects of Total Harmonics Distortion for Power Factor Correction at Non-Linear Load - R. A. Rani; Shakir Saat; Yusmarnita Yusop; Huzaimah Husin; F. K. Abdul Rahman; A. A. Isa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents the effect of total harmonic distortion (THD) in power factor correction (PFC) at non-linear load. This study focuses on the relationship between THD and PFC. This is beacuse,the power factor affects THD. This occurs in power system as we have variety of loads, i. e linear load or non-linear load. The variety of loads will influence the sinusoidal waveform, which comes out from harmonic distortion. Thus, based on this study, we can compare the effective method in improving the power factor as it will not disturb the performance of THD. The focus of study is on the single phase load, where the voltage restriction is 240 V.  The analysis will  only focus on the consumer, which depends on the variety of non-linear load. Besides, the parameters for analysis are based on the percentage of THD and the value of power factor. The instrument for measuring the parameter is based on power factor correction device or technique. On the other hand, the method that was used for this study is based on simulation which incorporated the Multisim software. At the end of ths study, we can choose the most effective method that can be used to improve the power factor correction without disturbing the THD.